Enhancing emotional support in human-robot interaction: Implementing emotion regulation mechanisms in a personal drone - Ori Fartook; Zachary McKendrick; Tal Oron-Gilad; Jessica R. Cauchard (Computers in Human Behavior: Artificial Humans)
We propose that social robots can enhance their social abilities by supporting peoples' emotional needs. We examined this concept by implementing four different mechanisms aimed at providing Emotional Support in a personal drone. These mechanisms (Affective Empathy, Cognitive Empathy, Positive Emotion Regulation (PER), and a Reasoning mechanism (yoU-turn)) provide various aspects of support ranging on the Emotional-Reasoning spectrum. In an online study (N = 95), first, participants were asked to sequentially recall situations where they experienced one of six emotional states (i.e., being calm, bored, excited, hyperactivated, scared, or sleepy).Following each induced emotion, participants ranked their preferred drone response to their specific emotional state. Results indicate that participants' preferences were based on the valence of their emotional state, emphasizing the need for social drones to have multiple response mechanisms to support their users. This work contributes to the field of human-robot interaction by implementing validated support mechanisms into a robotic system as its emotional responses.